Analyzing the impacts of competency, digitalization, and finance on the export performance of Micro, Small, and Medium Enterprises (MSMEs) - PANGESTU, Fajar Hadi (KDI School, 2023)
Micro, Small, and Medium Enterprises is one of the sectoral levels in Indonesia which negatively affected by COVID-19. MSMEs have important labor-intensive industries in Indonesia with a high level of employment and a significant share of GDP. This paper aims to analyze the impacts of competency, digitalization, and finance on the export of MSMEs in Indonesia to enhance export performance. The methodology in this research uses multiple linear regression on primary datasets. The methods are generated from a questionnaire survey on MSMEs developed by the Ministry of Trade Indonesia, the Bank of Indonesia, and the Directorate General of Customs and Excise Indonesia. The results provide evidence that competency and digitalization impact export performance. However, finance has not impacted the export performance. This finding could serve as a basis for the Indonesian government to shape more impactful policies to enhance the performance of MSMEs and determine the extension of MSME financing
Thesis(Master) -- KDI School: Master of Public Policy, 2023
Keywords: New business enterprises--Indonesia; Small business--Indonesia; Foreign trade promotion--Indonesia